Risk estimation for recurrent cardiovascular events using the SMART-REACH model and direct inpatient cost profiling in Indonesian ASCVD patients: a large-scale multicenter study - Dwiputra, Bambang; Desandri, Dwita Rian; Hartopo, Anggoro Budi; Juzar, Dafsah Arifa; Alkatiri, Amir Aziz; Zuhdi, Naufal; Ramadhan, Putra Andito; Kenconosari, Bernadhet Daisy; Phowira, Jason; Widyantoro, Bambang (Frontiers in Cardiovascular Medicine, 2024)
Introduction With atherosclerotic cardiovascular disease (ASCVD) cases increasing in Indonesia, there is a growing need to identify high-risk patients for recurrent cardiovascular events. Risk stratification could guide optimal secondary preventive therapy. Understanding the ASCVD direct inpatient costs could further provide insight in reducing the economic burden that comes with Indonesia's high number ASCVD cases. However, there is a significant gap in Indonesian large-scale research on both of these valuable data. Employing the SMART-REACH model, we can profile the risk of recurrent cardiovascular events in Indonesian ASCVD patients. Objectives Utilize the SMART-REACH model to estimate 10-year and lifetime risk of cardiovascular events in Indonesian ASCVD patients and describe the direct inpatient cost of ASCVD. Methods This descriptive cross-sectional study gathered data from 3,209 ASCVD patients aged 45–80 from two major cardiovascular centers using purposive sampling. Participants were patients admitted between January 2020 and March 2023 with ST-elevated myocardial infarct (STEMI), non-ST-elevated myocardial infarct (NSTEMI), and chronic coronary syndrome (CCS) requiring elective percutaneous coronary intervention (PCI). The SMART-REACH risk estimation model required clinical data upon admission, laboratory results within the first 24 h of admission, and cardiovascular medication prescribed upon discharge. The SMART-REACH model is a Fine and Gray competing risk model incorporating cardiovascular risk factors that estimates individual 10-year and lifetime risk for recurrent cardiovascular events which includes myocardial infarction, stroke, or vascular death. Direct inpatient cost profiling totaled all medical expenses incurred from ASCVD diagnosis admission to discharge. Results were reported descriptively with subgroup analyses. Results The cohorts (mean age 60.15 ± 8.6 years) were predominantly male [n = 2,537 (79.1%)], hypertensive [n = 2,267 (70.6%)], and diagnosed with STEMI [n = 1,732 (54%)]. The SMART-REACH model calculated a mean 10-year risk of 30.2% (95% CI 29.7–30.6) and a lifetime risk of 62.5% (95% CI 62.1–62.9). The direct inpatient cost of ASCVD patients includes a median 3,033 USD, with highest median costs in the STEMI subgroup (3,270 USD). Conclusions A significant number of Indonesian ASCVD patients exhibited notably high 10-year and lifetime risks of experiencing a major cardiovascular event. Combined with the direct inpatient cost, therapy optimization is crucially needed to mitigate these risks and further cost burden.